Does leverage predict delinquency in consumer lending? Evidence from Peru - Walter Cuba (Graduate Institute of International and Development Studies, 2020)
This paper examines to what extent household leverage - as measured by the debt-to-income (DTI) ratio - predicts delinquency in Peru's consumer credit market. A model is estimated to assess the relation between delinquency and the DTI ratio. The initial and current DTI ratios are assessed as delinquency predictors. The results confirm that the current DTI ratio is effective for predicting delinquency. This evidence supports its use in financial regulation to improve household credit risk assessment and control.
Keywords: G20; G21; D12; 330; Household finance; credit risk; consumer delinquency